Analisis Kinerja Finansial dan Nonfinansial Program Penanggulangan Kemiskinan Melalui KJKS BMT - Dewi Sartika (Journal of Applied Accounting and Taxation, 2017)
The poverty alleviation programs through KJKS BMT which was launched in 2010 as listed in APBD Padang City. This research is a descriptive research which used qualitative and quantitative approach. The purpose of this research is to know about the performance of financial and non financial as the program to overcome the poverty through KJKS BMT in Padang city. The researcher uses the primary and secondary data to gather the information for this research. For secondary data the researcher using several techniques, such as; semi structure interview technique, documentation technique, and observation technique. The data analysis method refers to the measurement of financial and non financial information performance. The benefits of this research are expected to make KJKS BMT as an intermediary between the media programs of poverty alleviation programs in community empowerment, forming a synergy between the programs with the same target group, and for the public, this study will be very useful for the general public to assess the seriousness and the performance of local governments in allocating the budget in an effort to overcome poverty. The results of the financial performance of the poverty alleviation program through KJKS BMT in Padang City from 2010 to 2015 showed an increase in value each year, the conditions were pretty good in 2011( 27.36%). Non-financial performance evaluation results by using the input indicator is 81.14% which means Very Good. The Indicator of the process was 74%, which means Good. Results of the assessment of the output indicator is at 90% which means Very Good. Finally, an indicator of impact is 66.67%, which means Good.